Antecedents of Satisfaction and Loyalty Towards In-App Purchase Intention for Indonesian Genshin Impact Players - Michele Gracia Rusli; Margaretha Pink Berlianto (Institute of Computer Science (IOCS), 2022)
The mobile game market has been increasing rapidly in the last five years. One of the most mobile game nowadays is Genshin Impact which has been awarded as the Best Mobile Game in 2021 by The Game Award. For games such as Genshin Impact, its source of income comes from in-app purchases and there are various factors that affecting the in-app purchase intention of the players such as satisfaction and loyalty that also can be affected by perceived value. A total of 271 Genshin Impact players from across Indonesia as samples were collected using the purposive sampling technique that involved online questionnaires with 5-point likert scale questions given to Genshin Impact players as its data collecting method. The data were analyzed using the statistical techniques known as structural equation modelling (SEM). The results of this study shows that Economic, Emotional, Hedonic, Utilitarian Values positively influence Satisfaction; Economic, Emotional, Hedonic, Utilitarian Values positively influence Loyalty; Satisfaction positively influence Loyalty; Loyalty positively influence Purchase Intention; Satisfaction does not positively influence Purchase Intention.